Guidelines for non-transplant chemotherapy for treatment of systemic AL amyloidosis: EHA-ISA working group. (2nd January 2023) - Wechalekar, Ashutosh D.; Cibeira, M. Teresa; Gibbs, Simon D.; Jaccard, Arnaud; Kumar, Shaji; Merlini, Giampaolo; Palladini, Giovanni; Sanchorawala, Vaishali; Schönland, Stefan; Venner, Christopher; Boccadoro, Mario; Kastritis, Efstathios
Abstract: Background: This guideline has been developed jointly by the European Society of Haematology and International Society of Amyloidosis recommending non-transplant chemotherapy treatment for patients with AL amyloidosis. Methods: A review of literature and grading of evidence as well as expert recommendations by the ESH and ISA guideline committees. Results and Conclusions: The recommendations of this committee suggest that treatment follows the clinical presentation which determines treatment tolerance tempered by potential side effects to select and modify use of drugs in AL amyloidosis. All patients with AL amyloidosis should be considered for clinical trials where available. Daratumumab-VCD is recommended from most untreated patients (VCD or VMDex if daratumumab is unavailable). At relapse, the two guiding principles are the depth and duration of initial response, use of a class of agents not previously exposed as well as the limitation imposed by patients' fitness/frailty and end organ damage. Targeted agents like venetoclax need urgent prospective evaluation. Future prospective trials should include advanced stage patients to allow for evidence-based treatment decisions. Therapies targeting amyloid fibrils or those reducing the proteotoxicity of amyloidogenic light chains/oligomers are urgently needed.